2011
DOI: 10.1074/jbc.m111.227660
|View full text |Cite
|
Sign up to set email alerts
|

Apo- and Cellopentaose-bound Structures of the Bacterial Cellulose Synthase Subunit BcsZ

Abstract: Cellulose, a very abundant extracellular polysaccharide, is synthesized in a finely tuned process that involves the activity of glycosyl-transferases and hydrolases. The cellulose microfibril consists of bundles of linear ␤-1,4-glucan chains that are synthesized inside the cell; however, the mechanism by which these polymers traverse the cell membrane is currently unknown. In Gram-negative bacteria, the cellulose synthase complex forms a trans-envelope complex consisting of at least four subunits. Although thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 38 publications
8
103
0
1
Order By: Relevance
“…This depressed activity may be a consequence of the incompatibility between the intrinsically compact structure of long polysaccharides and the requirement to bind in a thermodynamically disfavored extended conformation across an active site groove. The existence of polysaccharide aggregates has been previously suggested to result in low hydrolysis for the endo-acting GHs ExoK and ExsH from Rhizobium meliloti and BcsZ (16,66). In support of this hypothesis, BcsZ was more efficient at hydrolyzing in vitro synthesized cellulose in situ (67).…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofsupporting
confidence: 74%
See 2 more Smart Citations
“…This depressed activity may be a consequence of the incompatibility between the intrinsically compact structure of long polysaccharides and the requirement to bind in a thermodynamically disfavored extended conformation across an active site groove. The existence of polysaccharide aggregates has been previously suggested to result in low hydrolysis for the endo-acting GHs ExoK and ExsH from Rhizobium meliloti and BcsZ (16,66). In support of this hypothesis, BcsZ was more efficient at hydrolyzing in vitro synthesized cellulose in situ (67).…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofsupporting
confidence: 74%
“…The deep active site groove of PslG, lined with conserved surface-exposed aromatic residues, is analogous to the active site groove of BcsZ, which facilitates binding and catalysis of cellulose (16), and a carbohydrate-binding groove in the C-terminal domain of PgaB, a putative GH involved in PNAG biosynthesis (63). These features are common to processive, endoacting enzymes (64,65), and polysaccharide binding is observed in the grooves of both BcsZ and PgaB.…”
Section: Figure 7 Pslg Is Not Required For Psl Biosynthesis and Biofmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous metagenomic characterizations of bacterial communities in Atta and Acromyrmex gardens recovered mainly oligosaccharide-degrading enzymes and few CAZy families associated with the degradation of recalcitrant polysaccharides (17), suggesting that bacteria are not playing a prominent role in biomass degradation in fungus gardens. Moreover, our metaproteomic results revealed that although Ͼ81,000 spectra could be confidently mapped to diverse L. gongylophorus lignocellulases, only a single spectrum could be mapped to a bacterial GH8, a CAZyme family that in bacteria is often associated with cell wall modification rather than plant biomass degradation (49). Previous work identified a bacterial glucosidase produced in fungus gardens (17), however, and it remains a possibility that bacterial enzymes not present in the protein databases used in this study could be playing a role in biomass degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our analysis, at least 75% of the cellulases from GH8 are involved in the cellulose production in Proteobacteria. These cellulases may be involved in a transglycosylation reaction but have hydrolytic activity on cellulose analogs (e.g., carboxymethyl cellulose [CMC]) (31,39,57) and are thus frequently identified as hydrolytic cellulases. Although we have been careful in identifying putative biosynthetic enzymes, it is possible that other genes may have been misclassified, as some of these enzymes have been located outside the BCS operon (31) and/or as part of other GH families (39,40).…”
Section: Figmentioning
confidence: 99%